Hoosiers [videorecording (DVD)] - Anspaugh, David; Hackman, Gene; Hershey, Barbara, 1948-; Hopper, Dennis, 1936-2010; Wooley, Sheb, 1921-2003; Persons, Fern (MGM Home Entertainment, 2012)
A basketball coach with a checkered past leads him to a last-chance position with a last-chance team.